1984
DOI: 10.1128/jb.159.3.958-964.1984
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an alginase from mucoid strains of Pseudomonas aeruginosa

Abstract: Strains of Pseudomonas aeruginosa which produce an alginate-like slime polysaccharide were shown to also synthesize an intracellular enzyme which can degrade these polysaccharides and the seaweed alginic acids. The enzyme acts as an eliminase introducing delta 4,5 unsaturation into the uronic acid moiety. It appears to be a polymannuronide lyase which degrades the polysaccharides, depending on their uronic acid composition, to a series of oligosaccharides, the smallest of which is a disaccharide. L-Guluronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…3). Consistent with these data is the observation that the disaccharide is the smallest oligomer occurring after digestion of alginate with alginate lyase from P. aeruginosa [12]. This disaccharide results presumably from Lelimination of the pentamer catalysed by alginate lyase.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…3). Consistent with these data is the observation that the disaccharide is the smallest oligomer occurring after digestion of alginate with alginate lyase from P. aeruginosa [12]. This disaccharide results presumably from Lelimination of the pentamer catalysed by alginate lyase.…”
Section: Discussionsupporting
confidence: 68%
“…One hypothesis postulates that alginate lyase is providing primer for alginate synthesis [11]. The alginate lyase from P. aeruginosa has been characterized as a polymannuronate lyase, which acts on the mannuronate residue [12]. In order to get insight into catalytic properties of alginate lyase from mucoid P. aeruginosa, the lyase activity was analyzed with respect to de¢ned mannuronate oligomers as substrates, and the oligomer distribution was analyzed after alginate depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The alginate lyase enzyme itself is located in the periplasm. This therefore raises the question as to why the gene for the alginate lyase should be necessary and why there should be such a strong correlation between the production of alginate and of alginase [33,70]. This situation has also been found in the other alginate-producing Pseudomonas spp., P. fluorescens and P. putida [23].…”
Section: Other Biological Functionsmentioning
confidence: 99%
“…This enzyme of 39 kDa is found in the periplasm [107] of polysaccharide-producing strains of P. aeruginosa but appears to be absent from non-mucoid strains. In their experiments on P. aeruginosa polymannuronate lyase, Linker and Evans [70] found that the enzyme was relatively unstable and required high salt concentrations (c. 0.7 M sodium acetate) to maintain activity.…”
Section: Alginases From Azotobacter Speciesmentioning
confidence: 99%
“…One hypothesis postulates that alginate lyase is providing primer for alginate synthesis [11]. The alginate lyase from P. aeruginosa has been characterized as a polymannuronate lyase, which acts on the mannuronate residue [12]. In order to get insight into catalytic properties of alginate lyase from mucoid P. aeruginosa , the lyase activity was analyzed with respect to defined mannuronate oligomers as substrates, and the oligomer distribution was analyzed after alginate depolymerization.…”
Section: Introductionmentioning
confidence: 99%